Associative learning in Immatures and adults of generalist predators - OLIVEIRA, Cleber Macedo de (2012)
Plants produce organic volatiles continuously, however this blend of volatiles changes when they are infested by herbivores. These odours can be used by beneficial arthropods to locate prey. However, the blend of volatiles emitted by plants can vary with changing biotic and abiotic conditions. Due to variability of odours, it is expected that predators learn the association of odours and availability of food. Learning occurs when the response to an odour change due to an experience. Learning was demonstrated in many species of arthropods, however those studies assessed learning in adults. Those studies evaluated learning in the laboratory conditions and did not study the effect of the conditioned stimulus (i.e. odours) in the learning. Here, we aimed to study learning in immatures of the generalist predator Ceraeochrysa cubana and adults of Orius insidiosus. We assessed the effect of odours in the learning in two generalist predators and evaluated the effect of learning in the foraging behaviour of immature predators. We assessed the response of the predators to odours in the olfactometer and in a release-recapture experiment. The odours studied were methyl salicylate, rosemary oil liquid (Rosmarinus officinnalis) and mint oil. Immatures of lacewings learned the association of methyl salicylate with availability and unavailability of food. This was the first study that assessed the learning in immatures predators. Learning changed the foraging behaviour of immature predators. Immatures of lacewings were able to learn two association with the same odour, association of volatile with food and after association of volatile without food, during the immature phase. Additionally, our results showed that the learning ability of O. insidiosus is dependent of the conditioned stimulus (odours).